2020
DOI: 10.1186/s12939-020-01179-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of China’s 2009 healthcare reform on the utilisation of continuum of care for maternal health services: evidence from two cross-sectional household surveys in Shaanxi Province

Abstract: Background: Continuum of care for maternal health services (CMHS) is a proven approach to improve health and safety for mothers and newborns. This study aims to explore the influence of China's 2009 healthcare reform on improving the CMHS utilisation. Methods: This population-based cross-sectional quantitative study included 2332 women drawn from the fourth and fifth National Health Service Surveys of Shaanxi Province, conducted in 2008 and 2013 respectively, before and after China's 2009 healthcare reform. A … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
(48 reference statements)
1
4
0
Order By: Relevance
“…The RMMENT program, the Chinese version of the Safe Motherhood Program, reflected the government's strong political will and contributed to institutional births, thus narrowing the maternal health gap between urban and rural areas. Consistent with other studies, this study showed that the government-funded BPHS project contributed to prenatal examination rates [38], CMHS rates [31], and the hospital birth rate. We identified that the BPHS project was not significantly associated with postpartum visits, which is not in line with the findings of another study [38].…”
Section: The Determinants Of Maternal Healthcare Utilizationsupporting
confidence: 91%
See 1 more Smart Citation
“…The RMMENT program, the Chinese version of the Safe Motherhood Program, reflected the government's strong political will and contributed to institutional births, thus narrowing the maternal health gap between urban and rural areas. Consistent with other studies, this study showed that the government-funded BPHS project contributed to prenatal examination rates [38], CMHS rates [31], and the hospital birth rate. We identified that the BPHS project was not significantly associated with postpartum visits, which is not in line with the findings of another study [38].…”
Section: The Determinants Of Maternal Healthcare Utilizationsupporting
confidence: 91%
“…Adequate CMHS are critical for reducing maternal mortality [28]. Although there are many cross-sectional studies on ANC [29], hospital deliveries [24], or PNC [30], few articles explore the utilization of CMHS [31] and analyze the change in characteristics in different periods. Inadequate utilization of maternal health services remains severe in remote ethnic minority areas [32].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the portion of the low-income population that is unemployed or informally employed bears more of the burden of health care costs, which clearly results in inequity in the distribution of medical resources due to inequitable health insurance [31][32][33]. Moreover, some studies have found that the type of the health insurance affects equity in the use of health care services, such that the use of health care services differs among residents covered by different insurance policies [34][35][36][37].…”
Section: Gender Differences In Health Insurance and Health Statusmentioning
confidence: 99%
“…According to the China National Health Services Survey, the concentration index for outpatient and inpatient health service utilization in China in 2008 was 0.015 and 0.197, respectively, with higher-income groups using more outpatient and inpatient services [14]. This phenomenon is also present in outpatient and inpatient services for middle-aged and elderly groups [15], dental care for preschool children [16], and maternal health services for rural women [17].…”
Section: Introductionmentioning
confidence: 99%